Recurrent idiopathic chylothorax - Heda Melinda D Nataprawira; Oma Rosmayudi; Syaiful Effendy (Indonesian Pediatric Society Publishing House, 2016)
The chylous drainage may lead to high morbidity and may even compromise survival because of the large amount of loss, that is, deficits in lymphocytes, protein, and immunoglobulin. The treatment of chylothorax is still debatable with different therapeutic approaches i.e., purely conservative with elemental diet or total parenteral nutrition, or surgical (early or late) with ligation of the thoracic duct, pleurodesis, or placement of pleuroperitoneal shunts. The purpose of this report is to describe a case of chylothorax in a 2-year-old girl which was recurrent and difficult to manage.